Bone Scintigraphic Pattern and Correlation with Serum Prostate Specific Antigen Levels in Prostate Cancer Patients at NINMAS (Bangladesh Journal of Nuclear Medicine, 2024)
Abstract not availableBangladesh J. Nuclear Med. 27(1): 56-61, 2024